Shiny R : LiveLessons (LiveLessons (Indianapolis, Ind.), 2018)
"In Shiny R LiveLessons, Jared Lander shows you how to use Shiny to your advantage. Shiny is an open source web framework for R and Rstudio that enables you to turn analysis into visual, interactive applications. Shiny applications are easy to write and are built with R. No web development skills are necessary."--Resource description page